Highlighting the gap on spatial regulatory data in the official MPAs databases - Lippi, Simona; Piroddi, Chiara; Graziano, Mariagrazia; Di Franco, Antonio (Frontiers in Marine Science, 2024)
Marine protected areas (MPAs) are a cornerstone for conserving marine ecosystems. Legal instruments and directives have been put in place to foster conservation of species and habitats; among all, the development and implementation of a coherent network of effective MPAs. Spatial information on management measures and on regulated, forbidden or allowed activities are fundamental to understand the actual role of MPAs and to support/guide policy decisions. The shortage of standardized geospatial information on MPA management, governance features, and human uses hinders policy makers’ ability to make informed decisions regarding the designation, implementation and evaluation of marine associated policies. This policy brief aims to stimulate international actions to enable researchers and decision-makers accessing data for policy development, marine/maritime spatial planning and decision-making processes.